Uji Aktivitas Antioksidan Ekstrak Etanol dan Fraksi Etil Asetat Daun Renggak (Amomum dealbatum Roxb.) Dengan Metode ABTS - Radiartini, Ni Nyoman; Andayani, Yayuk; Deccati, Rizqa Fersiyana (Jurnal Farmasi & Sains Indonesia, 2024)
Renggak leaves (Amomum dealbatum Roxb.) contain secondary metabolites such as flavonoids, terpenoids, and tannins, which act as antioxidants. Previous research has shown that ethanol extract of renggak leaves has moderate antioxidant activity using the DPPH method. However, research on the antioxidant activity of the extract is limited, thus further investigation at the fraction level is needed. This study aims to identify the secondary metabolite content and antioxidant activity using the ABTS method (2,2-azinobis-3-ethylbenzothiazoline-6-sulfonic acid) of the ethanol extract and ethyl acetate fraction of renggak leaves. The renggak leaf samples were extracted using maceration with 96% ethanol (1:10), followed by fractionation with water, n-hexane, and ethyl acetate using a separatory funnel (1:1). Secondary metabolite screening was conducted on the ethanol extract and ethyl acetate fraction. Antioxidant activity was measured based on the reduction in absorbance at the ABTS maximum wavelength, expressed as IC50 (inhibitory concentration 50%) values, with ascorbic acid as a comparison. The secondary metabolite screening results indicated that both the ethanol extract and ethyl acetate fraction of renggak leaves contain alkaloids, flavonoids, tannins, and steroids. The antioxidant activity of the ethanol extract was very weak with an IC50 value of 236.11 ppm, whereas the antioxidant activity of the ethyl acetate fraction was strong with an IC50 value of 86,95 ppm, compared to the antioxidant activity of ascorbic acid with an IC50 value of 10,00 ppm.